HUBUNGAN ANTARA PENGETAHUAN IBU DUKUNGAN KELUARGA DAN DUKUNGAN PETUGAS KESEHATAN DENGAN KELENGKAPAN IMUNISASI DASAR PADA BAYI DAN BALITA DI RT 1-5 DUSUN SUNGAI BULUH WILAYAH KERJA PUSTU PULAU PALAS TAHUN 2019 - Madinah (STIKES HUSADA GEMILANG, 2019)
Immunization is to actively induce or increase a person’s immunity to a disease. Current immunization is to prevent about 2 to 3 million deaths each year. According to the data of Directorate for Disease Prevention and Control, Ministry of Health of the Republic of Indonesia, shows that there were 1.7 million children had not been immunized or incomplete immunized since 2014 to 2017. The purpose of the research is to analyze the correlation among the mothers’ knowledge, the family supports, the health workers supports, and the completeness of basic immunization on babies and toddlers in RT 1-5, Sungai Buluh, Pulau Palas. This research is an analytical descriptive with cross sectional study. The population and sample of the research were all mothers who have babies and toddlers. The sampling technique was accidental sampling (30 respondents). Data collection used questionnaire sheets. Data analysis was chi-square test with p < 0.05. The result verifies that the variables related to the completeness of the immunization was support provided by health workers (p value is 0.003 (p<0.05)). Accordingly, it is highly expected that the health workers cultivate collaboration with health cadres and local stakeholders to enrich mothers’ knowledge about the significance of immunization for babies and toddlers over counseling and discussion during posyandu. They are to perform good communication with family members (husband, mother, in-laws), so the family support can increase the coverage of complete basic immunization in babies and toddlers.